Psychopathological disorders in chronic cerebral ischemia: possibilities of prevention - O. V. Kotova; N. L. Zuykova; A. V. Palin; V. I. Frolova; E. V. Gushanskaya; I. V. Salyntsev; V. E. Medvedev (Лечащий Врач)
Anxiety, depression, somatoform disorders, nosogenic reactions, adjustment disorders, neurasthenia, somatogenic asthenia in patient with chronic cerebral ischemia (dyscirculatory encephalopathy, cerebrovascular disease) (CCI) are very important for the level of social functioning and adaptation. Early initiation of CCI therapy is an important task in preventing the progression not only of cerebrovascular pathology, but also a wide range of comorbid psychopathological disorders. Treatment of patients with CCI requires an individual approach taking into account pathogenetic factors and severity of both cognitive and psychopathological disorders. It should involve a wide range of drugs, including neuroprotectors. For this purpose the neuroprotective agents ethylmethyloxypyridine succinate and citicoline can be used for independent or combined use. Patients with various forms of CCI noticed subjective improvement during treatment which includes decreasing fatigability and general weakness, reduction of symptoms of psychic and somatic anxiety, fatigability, emotional lability, increasing activity and motivation, improvement of memory, attention, ability to concentrate that positively influences their professional activity.